Pengaruh Pemahaman Produk Dan Preferensi Terhadap Minat Masyarakat Menggunakan Jasa Perbankan Syariah - Ismail, Abdul Hadi; Pradesyah, Riyan (Yayasan Rahmat Islamiyah, 2024)
The uneven development of sharia financial institutions in North Sumatra has resulted in many people living in rural areas who do not understand sharia banking, only a small number of them only know about it from the closest people who live in urban areas, and recitations are often carried out. This research aims to test the variables Product Understanding (X1), Preference (X2) and Interest in using sharia banking services (Y). This research uses a quantitative research approach, with SPSS analysis tools. The results obtained show that there is a simultaneous influence of the variables Product Understanding (X1), Preference (X2), on people's interest in using sharia banking services (Y) of 61.9%.